Compressibilty and Young's modulus of filled joint - Abu Talib, Zaihasra (2005)
A number of the engineering structures such as tunnels, powerhouse cavern and mining shaft are constructed in the rock mass. The stability of these structures are greatly influenced by the engineering behaviour of the rock mass. For intact rock, its low deformability behaviour indicates that it is a stronger material. However, the condition changes with the presences of joint as discontinuity features in the rocks. The presence of this joint influence the strength and deformability of rock to a great extend. The situations become worst when intensive weathering of jointed rock mass under tropical climate leads the formation of the filled joint. Being the weakest component of a filled joint, filling materials contributes significantly to joint deformability and thus reducing joint strength and stiffness. In construction work that involving excavation in rock masses, filled joint poses a number of design and constructional problem that may influence the stability and factor of safety to the structure. Due to the above problems, a series of laboratory testing of physical models, which comprised of filled and unfilled joint, was carried-out. Comparing the stress-strain curves and Young's Modulus value has done analyses ofthe experimental result. The result suggested that the filled joint exhibits high deformation behaviour due to a lowest value of Young's Modulus. This behaviour contributed by the deformation and compressibility of the infilling material and as well as the deformation of joint blocks.